2013
DOI: 10.1186/1746-6148-9-35
|View full text |Cite
|
Sign up to set email alerts
|

Optimal specimen collection and transport methods for the detection of avian influenza virus and Newcastle disease virus

Abstract: BackgroundActive and passive surveillance for avian influenza virus (AIV) and Newcastle disease virus (NDV) is widespread in commercial poultry worldwide, therefore optimization of sample collection and transport would be valuable to achieve the best sensitivity and specificity possible, and to develop the most accurate and efficient testing programs. A H7N2 low pathogenicity (LP) AIV strain was selected and used as an indicator virus because it is present in lower concentrations in swabbings and thus requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Third, our models assumed perfect sensitivity and specificity of real-time RT-PCR for pooled samples. The assays used in this study are considered highly sensitive and specific (27,28), and previous studies did not report any differences in virus detection for pooled and individual samples (40)(41)(42). Furthermore, virus detection in our study was based on parallel interpretation of cloacal or oropharyngeal sample test results (i.e., positive if >1 was positive).…”
Section: Discussionmentioning
confidence: 85%
“…Third, our models assumed perfect sensitivity and specificity of real-time RT-PCR for pooled samples. The assays used in this study are considered highly sensitive and specific (27,28), and previous studies did not report any differences in virus detection for pooled and individual samples (40)(41)(42). Furthermore, virus detection in our study was based on parallel interpretation of cloacal or oropharyngeal sample test results (i.e., positive if >1 was positive).…”
Section: Discussionmentioning
confidence: 85%
“…The transport medium should be supplemented with antibiotics to avoid bacterial contamination during isolation. The swab material also influences the recovery of IAV, and flocked swabs are better than nonflocked swabs (38). Fixation of samples in ethanol (35) and sampling using FTA cards (22) are other preservation methods suitable for IAV surveillance and show advantages for biosafety and transportation, but analysis is limited to molecular screening and sensitivity between methods may vary.…”
Section: Discussionmentioning
confidence: 99%
“…Samples should ideally be frozen at the field site (using liquid nitrogen tanks or ultra-low-temperature freezers) or, if the necessary facilities are lacking, kept at ϩ4°C for a limited time until they are processed in the laboratory. Virus transport media, such as Hanks' balanced salt solution supplemented with protein or brain heart infusion (BHI) broth, increase the stability of the viruses (7,38) and are a preferred choice over phosphate-buffered saline (PBS) or dry swabs. The transport medium should be supplemented with antibiotics to avoid bacterial contamination during isolation.…”
Section: Discussionmentioning
confidence: 99%
“…With this method of detection, specimen processing requires nucleic acid stability rather than organism viability previously needed for culture. Many studies have compared various types of specimens, swabs, and processing buffers for influenza and other respiratory virus RT‐PCR assays [Abu‐Diab et al, ; Hernes et al, ; Irving et al, ; Spackman et al, ]. Laboratory‐based studies have found that influenza RNA was stable on dry swabs for days prior to processing if kept at room temperature or cooler [Moore et al, ; Druce et al, ].…”
Section: Introductionmentioning
confidence: 99%